(Sila)Difluoromethylation of Fluorenyllithium with CF3H and CF3TMS - Maruyama, Kenichi; Saito, Daichi; Mikami, Koichi (SynOpen, 2018)
Difluoromethylation of the C9-H site of the fluorene ring using lithium base and fluoroform (CF3H), which is one of the most cost-effective difluoromethylating reagents, is attained to give difluoromethylated fluorenes with an all-carbon quaternary center. The Ruppert–Prakash reagent (CF3TMS) can also be applied to the present reaction system, providing siladifluoromethylated fluorenes that can be utilized for sequential carbon–carbon bond-forming reactions through activation of the silyl group.
Keywords: fluoroform; Ruppert–Prakash reagent; bioisostere; fluorene; difluoromethylation; difluoromethyl; difluoromethylene; difluorocarbene